Penggunaan Metode Demonstrasi Sebagai Upaya Meningkatkan Hasil Belajar IPA Peserta Didik di Kelas IV SDN 208/X Simpang Tuan Semester Ganjil Tahun Pelajaran 2022/2023 - Yenny Yenny (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving science learning outcomes through the Demonstration method. This research is a classroom action research which consists of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementing, observing and reflecting. The subjects of this study were 20 class IV students at SDN 208/X Simpang Tuan. This research was conducted in the odd semester of the 2022/2023 academic year. Data collection techniques using tests, observation, and documentation. Data were analyzed using percentages. The results showed that the demonstration method could improve the science learning outcomes of class IV students at SDN 208/X Simpang Tuan by giving rewards